On viscoelastic fluid in a vertical porous media channel with Soret and Dufour effects. (February 2022) - Meng, Yahui; Li, Botong
Abstract: The time and spatial fractional constitutive models are employed to examine the flow, heat and mass transfer of a viscoelastic fluid flowing in a vertical porous media square channel accompanied by Soret and Dufour effects. The fractional modified Fourier's law and Fick's model are utilized to characterize the heat and mass transfer. The finite difference algorithm is used to calculate the governing equations. The numerical technique is validated and can be extended to solve similar problems. Results indicate that the enlargement of fractional derivative in momentum equation heightens the flow resistance between liquid molecules, while the increase of fractional derivative in temperature and concentration equations weakens the heat and mass transfer.